2019
DOI: 10.3390/cells8080831
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tks4 Knockout Mice Suggests a Role for Tks4 in Adipose Tissue Homeostasis in the Context of Beigeing

Abstract: Obesity and adipocyte malfunction are related to and arise as consequences of disturbances in signaling pathways. Tyrosine kinase substrate with four Src homology 3 domains (Tks4) is a scaffold protein that establishes a platform for signaling cascade molecules during podosome formation and epidermal growth factor receptor (EGFR) signaling. Several lines of evidence have also suggested that Tks4 has a role in adipocyte biology; however, its roles in the various types of adipocytes at the cellular level and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…These cell populations also contain MSCs. However, no difference was found between the adipogenic and osteogenic differentiation potential of cells isolated from TKS4 KO and wild-type mice [173]. Perhaps the complexity of the adipose tissue microenvironment (MSCs, preadipocytes, vascular endothelial cells, pericytes) together with the ECM can rescue the differentiation defects of TKS4 KO MSCs or preadipocytes (e.g., 3T3-L1 cells), which fail to properly differentiate in pure in vitro cultures.…”
Section: Cell Differentiation Modulated By Tks Moleculesmentioning
confidence: 93%
See 2 more Smart Citations
“…These cell populations also contain MSCs. However, no difference was found between the adipogenic and osteogenic differentiation potential of cells isolated from TKS4 KO and wild-type mice [173]. Perhaps the complexity of the adipose tissue microenvironment (MSCs, preadipocytes, vascular endothelial cells, pericytes) together with the ECM can rescue the differentiation defects of TKS4 KO MSCs or preadipocytes (e.g., 3T3-L1 cells), which fail to properly differentiate in pure in vitro cultures.…”
Section: Cell Differentiation Modulated By Tks Moleculesmentioning
confidence: 93%
“…A recent study revealed that TKS4 KO mice had a disturbed adipose depot phenotype involving the beige-ing/browning of white adipose tissue (WAT) depots and a concomitant "whitening" of brown adipose tissue (BAT) [173]. WAT was found to be enriched with smaller and more multi-locular adipocytes and showed higher expression of uncoupling protein 1 (UCP1) at both the RNA and protein levels in tissue samples of TKS4 KO mice compared with the same features in wild-type samples [173]. UCP1 is a marker of brown and beige adipocytes, which are responsible for uncoupling the mitochondrial respiratory chain to stimulate heat production instead of ATP generation [178].…”
Section: Role Of Tks4 In Tissue Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…The protein product of the SH3PXD2B gene, Tks4, belongs to the family of scaffold proteins [23]. Tks4 is involved in podosome formation, cell migration, mesenchymal stem cell differentiation, adipose tissue beigeing, and bone trabecular formation [23,24,25,26,27,28,29]. Inactivating mutations in the SH3PXD2B gene cause a rare genetic disorder known as Frank-ter-Haar syndrome (FTHS, OMIM:249420) [30].…”
Section: Introductionmentioning
confidence: 99%
“…In melanoma cells, both Tks4 and Tks5 were found to be necessary for the surface expression of membrane type-1 matrix metalloproteinase, thus promoting melanoma cell invasion and metastasis in vivo [ 15 ]. Tks4 plays a role in adipocyte differentiation, [ 18 ] and white and beige adipocyte biology [ 19 ]. By contrast, a role in neural-crest-derived cell type development has been attributed only to Tks5 [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%